The straight field line concept and applications - Ågren, O.; Moiseenk, V.E.; Hagnestål, A. (Вопросы атомной науки и техники, 2008)
The straight field line mirror field is a marginal minimum B field with straight nonparallel field lines. This field gives optimal ellipticity, the drift surfaces lie on a magnetic surface, radiofrequency heating of the plasma is predicted to be efficient and MHD stability is provided by the minimum B property. One intended application of the magnetic field configuration is energy production and transmutation of spent nuclear fuel in a fusion-fission machine, where the mirror confined plasma is surrounded by a fission mantle. Reactor safety can be increased with a subcritical fission mantle, and the fission power can exceed the fusion power by as much as a factor of 150 with a reasonable condition for reactor safety margins, and this provides a basis for a compact reactor design. The straight field line mirror concept can also be of interest as a plasma source for synthesis of sophisticated materials. Магнітне поле пастки з прямими, але непаралельними силовими лініями має максимум в центрі. Таке поле має мінімальну еліптичність магнітних поверхонь, дрейфові поверхні співпадають з магнітними, високочастотний нагрів може мати високу ефективність, та МГД- стійкість забезпечена мінімумом В. Одне з можливих застосувань такої магнітної конфігурації – виробництво електроенергії та трансмутація відпрацьованого ядерного палива в умовах, коли пастка знаходиться усередині ядерного реактора. Підвищена безпека роботи реактора забезпечується його підкритичністю, і коефіцієнт підсилення потужності досягає значення 150 з дотриманням вимог безпеки. Концепція утримання з прямими силовими лініями магнітного поля може також бути використаною в плазмових джерелах для синтезу складних матеріалів. Магнитное поле ловушки с прямыми, но непараллельными силовыми линиями имеет минимум в центре. Такое поле обладает минимальной эллиптичностью магнитных поверхностей, дрейфовые поверхности совпадают с магнитными, высокочастотный нагрев может иметь высокую эффективность, и МГД- устойчивость обеспечена минимумом В. Одно из возможных применений такой магнитной конфигурации – производство электроэнергии и трансмутация отработанного ядерного топлива в условиях, когда ловушка находится внутри ядерного реактора. Повышенная безопасность работы реактора обеспечивается его подкритичностью, и коэффициент усиления мощности достигает величины 150 при соблюдении требований безопасности. Концепция удержания с прямыми силовыми линиями магнитного поля может также быть использована в источниках плазмы для синтеза сложных материалов.